How to prepare for the TOEFL test : - Sharpe, Pamela J (Barron’s Educational, 1996)
The book includes eight full-length model tests with questions answered and explaned; a detail recommended study plan; An explanation of the TOEFL with time tables for both long and short forms; written transcript for the listening comprehension sections of tests